2017
DOI: 10.5194/bg-14-3633-2017
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of global warming through pH dependence of DMS production simulated with a fully coupled Earth system model

Abstract: Abstract. We estimate the additional transient surface warming T s caused by a potential reduction of marine dimethyl sulfide (DMS) production due to ocean acidification under the high-emission scenario RCP8.5 until the year 2200. Since we use a fully coupled Earth system model, our results include a range of feedbacks, such as the response of marine DMS production to the additional changes in temperature and sea ice cover. Our results are broadly consistent with the findings of a previous study that employed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 40 publications
3
51
1
Order By: Relevance
“…Culture experiments have confirmed that DMSP and DMS cell contents (normalized to cell volume) can be reduced by about 3 and 10 times in a dominant coccolithophorid species, Emiliania huxleyi, when exposed to doubled atmospheric CO 2 concentrations (Avgoustidi et al, 2012). In CALC, we reduced coccolithophore cellular organosulfur content in the DMS module by 90% for the high CO 2 scenario to provide a potential upper bound of the impact of ocean acidification on DMS production and compare with previous simulations by Six et al (2013) and Schwinger et al (2017). Simulated differences in DMS concentrations and other fields represent the consequences of an acidification-induced decline in ocean DMS production by coccolithophores.…”
Section: Ocean Acidification Simulation (Calc)supporting
confidence: 60%
See 3 more Smart Citations
“…Culture experiments have confirmed that DMSP and DMS cell contents (normalized to cell volume) can be reduced by about 3 and 10 times in a dominant coccolithophorid species, Emiliania huxleyi, when exposed to doubled atmospheric CO 2 concentrations (Avgoustidi et al, 2012). In CALC, we reduced coccolithophore cellular organosulfur content in the DMS module by 90% for the high CO 2 scenario to provide a potential upper bound of the impact of ocean acidification on DMS production and compare with previous simulations by Six et al (2013) and Schwinger et al (2017). Simulated differences in DMS concentrations and other fields represent the consequences of an acidification-induced decline in ocean DMS production by coccolithophores.…”
Section: Ocean Acidification Simulation (Calc)supporting
confidence: 60%
“…This is mostly attributable to different configurations of our simulations from Six et al (2013) as discussed previously, as well as missing feedback in the uncoupled simulations in Six et al (2013). Similarly, our simulated changes in radiative effect and temperature in CALC are smaller than results from Schwinger et al (2017), which suggested 0.19-0.30 W/m 2 changes of…”
Section: Climate Change Due To Biogenic Sulfur Emission Changesmentioning
confidence: 47%
See 2 more Smart Citations
“…2.4), hence allowing for a direct biogeochemical climate feedback in coupled simulations. The DMS air-sea flux is simulated as a function of upper-ocean biological production following the formulation of Six and Maier-Reimer (1996) and 135 was first tested in the NorESM model framework by Schwinger et al (2017).…”
Section: Introductionmentioning
confidence: 99%